Polite Language on Facebook: Maintaining Ethics in Interactions on Social Media - M, Asia (Borong Newinera Publisher, 2024)
The objective of this study was to examine the present condition of politeness in language usage on Facebook, determine the factors that impact the use of polite language, and suggest approaches to promote civility in digital interactions. Using a qualitative methodology, the data collection process involved analyzing the content of posts and comments from public Facebook pages and groups. Additionally, semi-structured interviews were conducted with users to gather their personal experiences and perceptions. Our analysis of the content uncovered notable disparities in the levels of politeness observed. Community-oriented groups demonstrated elevated levels of politeness, likely attributed to their shared interests and established norms. Conversely, discussions centered around political matters were more susceptible to impoliteness, largely influenced by the anonymity of participants and the intensity of emotions involved. Interviews emphasized the significance of cultural variations, the design features of Facebook, and the crucial role of personal responsibility in upholding politeness. Effective moderation and well-defined guidelines were determined to be essential in handling discourteous conduct. The results highlight the importance of adopting a holistic strategy towards digital communication, encompassing the promotion of cultural sensitivity, the improvement of digital literacy, and the development of ethical platform features. These measures aim to cultivate a more respectful and constructive online environment.